2006
DOI: 10.2516/ogst:2006032a
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of H2S on Volcano Curves in Hydrotreating Sulfide Catalysis

Abstract: Résumé -Effet dual d'H 2 S sur les courbes en volcan en catalyse d'hydrotraitement -Les progrès récents des techniques de modélisation moléculaire quantique ont permis l'interprétation rationnelle des tendances périodiques observées en catalyse par les sulfures de métaux de transition. Les courbes en volcan obtenues de façon empirique peuvent être expliquées par des modélisations microcinétiques inté-grant des descripteurs chimiques judicieux calculés ab initio. Cette approche a été appliquée avec succès en ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Mixed Co(Ni)-Mo sites present at the M-edge exhibit intermediate sulfur-metal bond energy values comprised between non-promoted Mo-site and pure Co site. Recent microkinetic investigations of the toluene hydrogenation on various transition metal sulfide catalysts have shown that a volcano curve correlates well the intrinsic catalytic activities with their sulfur-metal bond energies [29]. As a consequence, intermediate sulfur-metal bond energies of mixed Co(Ni)-Mo sites provide the optimal surface concentrations for the reactive species involved in the kinetically limiting step of toluene hydrogenation: -SH groups and toluene.…”
Section: Tablementioning
confidence: 98%
“…Mixed Co(Ni)-Mo sites present at the M-edge exhibit intermediate sulfur-metal bond energy values comprised between non-promoted Mo-site and pure Co site. Recent microkinetic investigations of the toluene hydrogenation on various transition metal sulfide catalysts have shown that a volcano curve correlates well the intrinsic catalytic activities with their sulfur-metal bond energies [29]. As a consequence, intermediate sulfur-metal bond energies of mixed Co(Ni)-Mo sites provide the optimal surface concentrations for the reactive species involved in the kinetically limiting step of toluene hydrogenation: -SH groups and toluene.…”
Section: Tablementioning
confidence: 98%
“…H 2 S in uence on the HDS reaction has been discussed extensively in various studies [29][30][31][32][33][34][35], which consensually suggested that H 2 S suppresses the DDS route, whilst having very little impact on the HYD route. In contrast, several research groups, including our own, have reported that some transition metal sul de catalysts can e ectively promote the HYD reaction when they are carried out in the presence of H 2 S [36][37][38]. Guernalec et al [38] correlated this positive behavior to the increase of the -SH concentration on the catalyst surface.…”
Section: Impact Of H 2 Smentioning
confidence: 67%
“…In contrast, several research groups, including our own, have reported that some transition metal sul de catalysts can e ectively promote the HYD reaction when they are carried out in the presence of H 2 S [36][37][38]. Guernalec et al [38] correlated this positive behavior to the increase of the -SH concentration on the catalyst surface. However, our obtained results represent a unique catalytic Figure 6: E ect of the Co content on the HDS activity (a) and the relationship between the activity and the selectivity (b).…”
Section: Impact Of H 2 Smentioning
confidence: 67%
“…These TMS present a nearly spherical shape. Due to its crystallographic properties, rhombohedral Cr2S3 forms rather large plate -like particles as observed by Figure 2 [21,22].…”
Section: Tms/hy Preparation and Characterizationmentioning
confidence: 99%
“…The concentrations of Brönsted and Lewis acid sites after desorption at 150,250 and 350 °C were calculated using the extinction coefficients εBA (1.67) and εLA (2.22) determined by Emeis et al 23 As compared to the zeolitic support alone, the introduction of the TMS generally reduces the Brönsted acidic site (BAS) content and strength except in the case of RuS2 with an increase of BAS and with Cr sulfide where a high content of Lewis site was found. This sulfide belongs exhibit a low M-S bond strength [21] and the lamellar particles can be easily reduced at the surface to generate Lewis sites. For the variations observed on the other sulfides, we do not have yet any clear explanation.…”
Section: Tms/hy Preparation and Characterizationmentioning
confidence: 99%